Analysis of Student Difficulty Levels in Solving Spatial Structure Problems for Grade IX Students at SMPN 2 Krounjendit Mindiptana - Bonaso Bonaso*; Hotmaulina Sihotang (Riwayat: Educational Journal of History and Humanities, 2023)
This study is an analysis of the level of difficulty students encounter in solving mathematical problems related to spatial structures at SMPN 2 Krounjendit Mindiptana. The research aims to identify the types of difficulties experienced by students and to determine their mathematical problem-solving abilities. The method employed in this study is experimentation. Data collection techniques involve the use of test instruments and in-depth interviews with students. Data analysis employs descriptive statistics to provide a clear overview of the difficulties experienced by students and their mathematical problem-solving abilities. The research was conducted with 24 students, while 4 students were interviewed. Based on the analysis, it was found that 67% of the students were unable to comprehend the problems presented in each item, 58% struggled with planning problem-solving approaches, 71% had difficulties with calculations involved in mathematical problem-solving, and 79% of students did not review their answers after solving mathematical problems. Furthermore, findings from the interviews revealed that all interviewed students expressed a lack of understanding in spatial structures learning and a deficiency in memory when applying concepts or formulas in mathematical problem-solving.